Schwarzites carbon-loaded nano silicon material as well as preparation method and application thereof
By using ZTC structural molecular sieve templates to prepare Schwarzites carbon-loaded nanosilicon materials with high SP2 carbon content, the problem of insufficient flexibility of nanosilicon loaded porous carbon materials in lithium-ion batteries is solved, and better negative electrode sheet stability and charge and discharge performance are achieved. .
Patent Information
- Application Number
- CN202411245550.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-20
AI Technical Summary
The flexibility of nano-silicon-loaded porous carbon materials in existing lithium-ion batteries is poor, resulting in easy breakage during the rolling process of negative electrode sheets and difficult to suppress the volume expansion of silicon particles.
Using molecular sieve with ZTC structure as template, Schwarzites carbon-loaded nanosilicon material is prepared by chemical vapor deposition method, which improves SP2 carbon content and chemical bond strength, enhances the flexibility of the material, and forms a tight and regular structure through carbon coating technology, suitable for negative electrodes. piece.
It effectively alleviates the crushing problem of the negative electrode sheet during the rolling process, and better inhibits the volume expansion of silicon particles during the charging and discharging process, improving the mechanical properties of the material.
Smart Images

Figure CN119170728A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to Schwarzites carbon-loaded nano-silicon materials and a preparation method and application thereof. Background Art
[0002] Silicon-carbon materials formed by nano-silicon loaded porous carbon have high specific capacity and high initial coulombic efficiency, and are considered as potential materials for negative electrodes of high energy density lithium-ion batteries. However, porous carbon materials prepared by chemical activation and high-temperature carbonization are currently limited due to their low specific capacity and high initial coulombic efficiency. 2 The carbon content is less than 50%, resulting in poor mechanical properties, especially poor flexibility, which makes the silicon-carbon material easy to break during the rolling process of the negative electrode sheet, and it is difficult to suppress the volume expansion of silicon particles during the charging and discharging process. Summary of the invention
[0003] Based on this, it is necessary to provide a Schwarzites carbon-loaded nano-silicon material and a preparation method and application thereof to address the problem of poor flexibility of silicon-carbon materials in the prior art.
[0004] The present invention provides a method for preparing Schwarzites carbon-loaded nano-silicon material, comprising the following steps:
[0005] Using a molecular sieve with a ZTC structure as a template, chemical vapor deposition is carried out under the conditions of a protective atmosphere and a gaseous carbon source to obtain a molecular sieve-carbon composite material;
[0006] removing the template in the molecular sieve-carbon composite material to obtain Schwarzites carbon;
[0007] Using Schwarzites carbon as a carrier, chemical vapor deposition is carried out under the conditions of a protective atmosphere and a gas-phase silicon source to obtain a silicon-carbon composite material;
[0008] The silicon-carbon composite material is carbon-coated to obtain Schwarzites carbon-loaded nano-silicon material.
[0009] In one embodiment, the ZTC structured molecular sieve is at least one of zeolite LTA molecular sieve, zeolite FAU molecular sieve or zeolite EMT molecular sieve.
[0010] In one embodiment, the D of the ZTC structured molecular sieve is 50 5μm-20μm.
[0011] In one embodiment, the step of performing chemical vapor deposition under the conditions of a protective atmosphere and a gaseous carbon source satisfies at least one of the following conditions:
[0012] (1) The gaseous carbon source is selected from at least one of acetylene, methane, ethylene, benzene or toluene;
[0013] (2) The temperature of chemical vapor deposition is 500°C-2000°C and the time is 0.5h-10h;
[0014] (3) The heating rate of chemical vapor deposition is 1℃ / min-10℃ / min;
[0015] (4) The protective atmosphere is selected from at least one of nitrogen and inert gas.
[0016] In one embodiment, the template in the molecular sieve-carbon composite material is removed by alkali washing or water washing at a temperature of 50°C-150°C.
[0017] In one embodiment, the step of performing chemical vapor deposition under the conditions of a protective atmosphere and a gas phase silicon source satisfies at least one of the following conditions:
[0018] (1) The gas phase silicon source is selected from at least one of silane, disilane, dichlorosilane or tetramethylsilane;
[0019] (2) The temperature of chemical vapor deposition is 400°C-650°C and the time is 0.5h-5h;
[0020] (3) The heating rate of chemical vapor deposition is 1℃ / min-10℃ / min;
[0021] (4) The protective atmosphere is selected from at least one of nitrogen and inert gas.
[0022] In one embodiment, the silicon-carbon composite material is carbon-coated by chemical vapor deposition, wherein the chemical vapor deposition step satisfies at least one of the following conditions:
[0023] (1) the gaseous carbon source is selected from at least one of acetylene, methane, ethylene, benzene or toluene;
[0024] (2) The heating rate of chemical vapor deposition is 1℃ / min-10℃ / min;
[0025] (3) The temperature of chemical vapor deposition is 500°C-1000°C, and the time is 0.5h-3h;
[0026] (4) Chemical vapor deposition is carried out under a protective atmosphere, wherein the protective atmosphere is selected from at least one of nitrogen or an inert gas.
[0027] The present invention also provides a Schwarzites carbon-loaded nano-silicon material prepared by adopting the preparation method of the Schwarzites carbon-loaded nano-silicon material.
[0028] The present invention also provides a negative electrode sheet prepared by using the Schwarzites carbon-loaded nano-silicon material.
[0029] The present invention also provides a secondary battery prepared by using the negative electrode sheet.
[0030] The present invention uses a ZTC structured molecular sieve as a template. The ZTC structured molecular sieve has a rich, unique and uniform pore structure and has a strong adsorption capacity. In the process of chemical vapor deposition, it can not only reduce the deposition of carbon source gas in non-predetermined areas, but also induce the orderly growth of carbon atoms, thereby obtaining Schwarzites carbon and improving SP 2 High carbon content, and due to SP 2 Carbon has a shorter bond length, which makes the chemical bond strength of Schwarzites carbon high, and the covalent bond directionality is strong. The structure formed is more compact and regular, and can withstand greater external force extrusion. Therefore, while meeting the requirements of porous carbon pore volume and pore size, it can improve flexibility. In addition, Schwarzites carbon retains the strong adsorption characteristics of the molecular sieve with ZTC structure, which is conducive to the deposition of nano-silicon. Furthermore, when the Schwarzites carbon-loaded nano-silicon material obtained by using Schwarzites carbon as a carrier is applied to the negative electrode sheet, it can effectively alleviate its breakage problem during the rolling process, and at the same time, it can better suppress the volume expansion of silicon particles during the charge and discharge process. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is the Raman spectrum of the Schwarzites carbon prepared in Example 3;
[0032] Figure 2 is the Raman spectrum of the Schwarzites carbon prepared in Example 8;
[0033] Figure 3 The Raman spectrum of the biomass porous carbon prepared in Comparative Example 1;
[0034] Figure 4 This is the first cycle charge and discharge test graph of the Schwarzites carbon-supported nano-silicon material prepared in Example 3, where A is the discharge curve and B is the charge curve;
[0035] Figure 5 This is the first cycle charge and discharge test graph of the Schwarzites carbon-supported nano-silicon material prepared in Example 8, where A is the discharge curve and B is the charge curve;
[0036] Figure 6 This is the first cycle charge and discharge test diagram of the biomass porous carbon-loaded nano-silicon material prepared in Comparative Example 1, where A is the discharge curve and B is the charge curve. DETAILED DESCRIPTION
[0037] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0039] The method for preparing Schwarzites carbon-loaded nano-silicon material provided by the present invention comprises the following steps:
[0040] S1, using a ZTC structured molecular sieve as a template, chemical vapor deposition is performed under the conditions of a protective atmosphere and a gaseous carbon source to obtain a molecular sieve-carbon composite material;
[0041] S2, removing the template in the molecular sieve-carbon composite material to obtain Schwarzites carbon;
[0042] S3, using Schwarzites carbon as a carrier, chemical vapor deposition is carried out under the conditions of a protective atmosphere and a gas-phase silicon source to obtain a silicon-carbon composite material;
[0043] S4, carbon-coating the silicon-carbon composite material to obtain Schwarzites carbon-loaded nano-silicon material.
[0044] The molecular sieve with ZTC structure has rich, unique and uniform pore structure and strong adsorption. In step S1 of the present invention, the molecular sieve with ZTC structure is used as a template, which can not only reduce the deposition of carbon source gas in non-predetermined areas during chemical vapor deposition, but also induce the orderly growth of carbon atoms, thereby obtaining Schwarzites carbon and improving SP 2 High Carbon Content, Specific, Schwarzites Carbon Medium SP 2 The carbon content is more than 80%, and due to SP 2Carbon has a shorter bond length, which makes the chemical bond strength of Schwarzites carbon high and the covalent bond directionality strong. The formed structure is more compact and regular, and can withstand greater external force. Therefore, while meeting the requirements of porous carbon pore volume and pore size, the flexibility can be improved.
[0045] Optionally, the molecular sieve of the ZTC structure is selected from at least one of zeolite LTA type molecular sieve, zeolite FAU type molecular sieve or zeolite EMT type molecular sieve, and the D 50 Preferably, it is 5 μm to 20 μm.
[0046] In the step of performing chemical vapor deposition under the conditions of a protective atmosphere and a gaseous carbon source, the gaseous carbon source is selected from at least one of acetylene, methane, ethylene, benzene or toluene, and the protective atmosphere is selected from at least one of inert gases such as nitrogen or argon.
[0047] The temperature of chemical vapor deposition is 500°C-2000°C, the time is 0.5h-10h, and the heating rate of chemical vapor deposition is 1°C / min-10°C / min.
[0048] In step S2, the template in the molecular sieve-carbon composite material is removed to obtain Schwarzites carbon.
[0049] Optionally, the template in the molecular sieve-carbon composite material is removed by alkali washing or water washing at a temperature of 50° C.-150° C., wherein an alkaline solution such as potassium hydroxide or sodium hydroxide is preferably used for alkali washing.
[0050] The Schwarzites carbon prepared by steps S1 and S2 retains the strong adsorption characteristics of the molecular sieve with a ZTC structure. Therefore, in step S3, when chemical vapor deposition is performed using the Schwarzites carbon as a carrier under the conditions of a protective atmosphere and a gas-phase silicon source, it is beneficial to the deposition of nano-silicon.
[0051] Optionally, in the step of performing chemical vapor deposition under the conditions of a protective atmosphere and a gaseous silicon source, the gaseous silicon source is selected from at least one of silane, disilane, dichlorosilane or tetramethylsilane, and the protective atmosphere is selected from at least one of inert gases such as nitrogen or argon.
[0052] The temperature of chemical vapor deposition is 400°C-650°C, the time is 0.5h-5h, and the heating rate of chemical vapor deposition is 1°C / min-10°C / min.
[0053] In step S4, the silicon-carbon composite material is preferably carbon-coated by chemical vapor deposition, wherein in the step of chemical vapor deposition, the gaseous carbon source is selected from at least one of acetylene, methane, ethylene, benzene or toluene, the protective atmosphere is selected from at least one of inert gases such as nitrogen or argon, the heating rate of chemical vapor deposition is 1°C / min-10°C / min, the temperature of chemical vapor deposition is 500°C-1000°C, and the time is 0.5h-3h.
[0054] The present invention uses a molecular sieve with a ZTC structure as a template to induce the growth of carbon materials to obtain SP 2 The carbon content of Schwarzites carbon is more than 80%. Schwarzites carbon has excellent flexibility and is conducive to the deposition of nano-silicon.
[0055] Furthermore, the specific surface area of the ZTC structured molecular sieve is preferably 500 m 2 / g-1500m 2 / g, pore volume is 0.1cm 3 / g-0.8cm 3 / g, the pore size is 0.3nm-5nm, the pore size of the obtained Schwarzites carbon is 0.5nm-5nm, and the pore volume is 0.1cm 3 / g-0.5cm 3 / g, specific surface area is 800m 2 / g-2000m 2 / g, has a better effect.
[0056] The present invention also provides a Schwarzites carbon-loaded nano-silicon material prepared by adopting the preparation method of the Schwarzites carbon-loaded nano-silicon material.
[0057] The present invention also provides a negative electrode sheet prepared by using the Schwarzites carbon-loaded nano-silicon material.
[0058] The preparation method of the negative electrode sheet is as follows: the Schwarzites carbon-loaded nano-silicon material, the conductive agent and the binder are mixed in proportion to form a slurry, the slurry is coated on a current collector, and the negative electrode sheet is obtained by drying.
[0059] Optionally, the conductive agent is selected from at least one of acetylene black, Ketjen black or Super P; the binder is selected from at least one of sodium carboxymethyl cellulose, sodium alginate or polyvinylidene fluoride, preferably sodium carboxymethyl cellulose and Super P; the solvent used for the negative electrode slurry is water; the current collector is selected from at least one of copper foil or aluminum foil.
[0060] The present invention also provides a secondary battery prepared by using the negative electrode sheet. The secondary battery can be a lithium ion battery or the like.
[0061] Wherein, the lithium-ion battery structure includes the negative electrode sheet, the positive electrode sheet, the separator and the electrolyte. Optionally, the electrolyte includes a lithium salt and a non-aqueous solvent. The lithium salt is selected from at least one of LiPF6 or LiBF4. Preferably, the lithium salt is LiPF6. The non-aqueous solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate or diethyl carbonate, preferably a mixture of diethyl carbonate and ethylene carbonate.
[0062] Since Schwarzites carbon has excellent flexibility, when the Schwarzites carbon-loaded nano-silicon material obtained by using Schwarzites carbon as a carrier is applied to the negative electrode sheet, it can effectively alleviate its breakage problem during the rolling process, and at the same time, it can better suppress the volume expansion of silicon particles during the charging and discharging process.
[0063] Hereinafter, the Schwarzites carbon-supported nano-silicon material and its preparation method and application will be further described through the following specific examples.
[0064] Example 1
[0065] D 50 A zeolite LTA molecular sieve with a size of 5 μm was placed in a nitrogen atmosphere and heated to 1000°C at a heating rate of 5°C / min. Acetylene gas was then introduced for 3 hours, then switched to nitrogen and cooled to room temperature to obtain a molecular sieve-carbon composite material.
[0066] The molecular sieve-carbon composite material is placed in a sodium hydroxide aqueous solution and kept at 70° C. for 12 hours to remove the zeolite LTA type molecular sieve and obtain Schwarzites carbon.
[0067] The Schwarzites carbon was placed in a nitrogen atmosphere, heated to 450°C at a heating rate of 5°C / min, and then switched to silane gas for 3 hours. Then, the nitrogen gas was switched and the temperature was raised to 600°C at a heating rate of 5°C / min. The nitrogen gas was stopped and switched to acetylene gas. After 1 hour, the nitrogen gas was switched to nitrogen, and the temperature was lowered to room temperature in a nitrogen atmosphere to obtain Schwarzites carbon-loaded nanosilicon material.
[0068] Example 2
[0069] D 50 A zeolite LTA molecular sieve with a size of 7 μm was placed in a nitrogen atmosphere and heated to 1200°C at a heating rate of 5°C / min. Acetylene gas was then introduced for 3 hours, then switched to nitrogen and cooled to room temperature to obtain a molecular sieve-carbon composite material.
[0070] The molecular sieve-carbon composite material is placed in a sodium hydroxide aqueous solution and kept at 70° C. for 12 hours to remove the zeolite LTA type molecular sieve and obtain Schwarzites carbon.
[0071] The Schwarzites carbon was placed in a nitrogen atmosphere, heated to 450°C at a heating rate of 5°C / min, and then switched to silane gas for 3 hours. Then, the nitrogen gas was switched and the temperature was raised to 600°C at a heating rate of 5°C / min. The nitrogen gas was stopped and switched to acetylene gas. After 1 hour, the nitrogen gas was switched to nitrogen, and the temperature was lowered to room temperature in a nitrogen atmosphere to obtain Schwarzites carbon-loaded nanosilicon material.
[0072] Example 3
[0073] D 50 A zeolite LTA molecular sieve with a size of 7 μm was placed in a nitrogen atmosphere and heated to 1500°C at a heating rate of 2°C / min. Acetylene gas was then introduced for 3 hours, then switched to nitrogen and cooled to room temperature to obtain a molecular sieve-carbon composite material.
[0074] The molecular sieve-carbon composite material is placed in a sodium hydroxide aqueous solution and kept at 70° C. for 12 hours to remove the zeolite LTA type molecular sieve and obtain Schwarzites carbon.
[0075] The Schwarzites carbon was placed in a nitrogen atmosphere, heated to 500°C at a heating rate of 5°C / min, and then switched to silane gas for 3 hours. Then, the nitrogen gas was switched and the temperature was increased to 700°C at a heating rate of 10°C / min. The nitrogen gas was stopped and switched to acetylene gas. After 1 hour, the gas was switched to nitrogen and the temperature was lowered to room temperature in a nitrogen atmosphere to obtain Schwarzites carbon-loaded nanosilicon material.
[0076] Example 4
[0077] D 50 A zeolite FAU molecular sieve with a size of 10 μm was placed in a nitrogen atmosphere and heated to 1500°C at a heating rate of 2°C / min. Acetylene gas was then introduced for 3 hours, then switched to nitrogen and cooled to room temperature to obtain a molecular sieve-carbon composite material.
[0078] The molecular sieve-carbon composite material is placed in a sodium hydroxide aqueous solution and kept at 100° C. for 12 hours to remove the zeolite FAU type molecular sieve and obtain Schwarzites carbon.
[0079] The Schwarzites carbon was placed in a nitrogen atmosphere, heated to 500°C at a heating rate of 5°C / min, and then switched to silane gas for 3 hours. Then, the nitrogen gas was switched and the temperature was increased to 700°C at a heating rate of 10°C / min. The nitrogen gas was stopped and switched to acetylene gas. After 1 hour, the gas was switched to nitrogen and the temperature was lowered to room temperature in a nitrogen atmosphere to obtain Schwarzites carbon-loaded nanosilicon material.
[0080] Example 5
[0081] D 50 A zeolite FAU molecular sieve with a size of 10 μm was placed in a nitrogen atmosphere and heated to 1700°C at a heating rate of 2°C / min. Methane gas was then introduced for 5 hours, and then switched to nitrogen and cooled to room temperature to obtain a molecular sieve-carbon composite material.
[0082] The molecular sieve-carbon composite material is placed in a sodium hydroxide aqueous solution and kept at 100° C. for 12 hours to remove the zeolite FAU type molecular sieve and obtain Schwarzites carbon.
[0083] The Schwarzites carbon was placed in a nitrogen atmosphere, heated to 550°C at a heating rate of 5°C / min, and then switched to silane gas for 3 hours. Then, the nitrogen gas was switched and the temperature was increased to 700°C at a heating rate of 10°C / min. The nitrogen gas was stopped and switched to acetylene gas. After 1 hour, the gas was switched to nitrogen and the temperature was lowered to room temperature in a nitrogen atmosphere to obtain Schwarzites carbon-loaded nanosilicon material.
[0084] Example 6
[0085] D 50 A zeolite FAU molecular sieve with a size of 10 μm was placed in a nitrogen atmosphere and heated to 2000°C at a heating rate of 2°C / min. Methane gas was then introduced for 5 hours, and then switched to nitrogen and cooled to room temperature to obtain a molecular sieve-carbon composite material.
[0086] The molecular sieve-carbon composite material is placed in a sodium hydroxide aqueous solution and kept at 100° C. for 12 hours to remove the zeolite FAU type molecular sieve and obtain Schwarzites carbon.
[0087] The Schwarzites carbon was placed in a nitrogen atmosphere, heated to 550°C at a heating rate of 5°C / min, and then switched to silane gas for 3 hours. Then, the nitrogen gas was switched and the temperature was increased to 700°C at a heating rate of 10°C / min. The nitrogen gas was stopped and switched to acetylene gas. After 1 hour, the gas was switched to nitrogen and the temperature was lowered to room temperature in a nitrogen atmosphere to obtain Schwarzites carbon-loaded nanosilicon material.
[0088] Example 7
[0089] D 50 A zeolite EMT molecular sieve with a size of 10 μm was placed in a nitrogen atmosphere, heated to 2000°C at a heating rate of 2°C / min, and then switched to methane gas for 5 hours. The gas was then switched to nitrogen and cooled to room temperature to obtain a molecular sieve-carbon composite material.
[0090] The molecular sieve-carbon composite material is placed in a sodium hydroxide aqueous solution and kept at 150° C. for 12 hours to remove the zeolite EMT type molecular sieve and obtain Schwarzites carbon.
[0091] The Schwarzites carbon was placed in a nitrogen atmosphere, heated to 550°C at a heating rate of 5°C / min, and then switched to silane gas for 3 hours. Then, the nitrogen gas was switched and the temperature was increased to 700°C at a heating rate of 10°C / min. The nitrogen gas was stopped and switched to acetylene gas. After 1 hour, the gas was switched to nitrogen and the temperature was lowered to room temperature in a nitrogen atmosphere to obtain Schwarzites carbon-loaded nanosilicon material.
[0092] Example 8
[0093] D 50 A zeolite EMT molecular sieve with a size of 10 μm was placed in a nitrogen atmosphere, heated to 2000°C at a heating rate of 2°C / min, and then switched to methane gas for 5 hours. The gas was then switched to nitrogen and cooled to room temperature to obtain a molecular sieve-carbon composite material.
[0094] The molecular sieve-carbon composite material is placed in a sodium hydroxide aqueous solution and kept at 150° C. for 12 hours to remove the zeolite EMT type molecular sieve and obtain Schwarzites carbon.
[0095] The Schwarzites carbon was placed in a nitrogen atmosphere, heated to 600°C at a heating rate of 10°C / min, and then replaced with disilane gas for 3 hours. Then, the nitrogen gas was replaced and the temperature was increased to 800°C at a heating rate of 10°C / min. The nitrogen gas was stopped and replaced with acetylene gas. After 1 hour, the gas was replaced with nitrogen, and the temperature was lowered to room temperature in a nitrogen atmosphere to obtain Schwarzites carbon-loaded nanosilicon material.
[0096] Comparative Example 1
[0097] The biomass coconut shell was placed in a nitrogen atmosphere, heated to 700°C at a heating rate of 5°C / min and carbonized for 2 hours, cooled to room temperature in a nitrogen atmosphere, crushed, and passed through a 400-mesh sieve to obtain a carbonized material.
[0098] The carbonized material and potassium hydroxide were mixed in a mass ratio of 1:1 and placed in a nitrogen atmosphere. The mixture was heated to 800°C at a heating rate of 5°C / min for activation for 3 hours. The mixture was then washed several times with hydrochloric acid and deionized water and dried to obtain biomass porous carbon.
[0099] The porous carbon was placed in a nitrogen atmosphere, heated to 500°C at a heating rate of 5°C / min, switched to disilane gas, kept warm for 3 hours, then switched to nitrogen, and heated to 700°C at a heating rate of 10°C / min. Thereafter, the nitrogen was changed to acetylene gas, kept warm for 1 hour, then switched to nitrogen, and cooled to room temperature to obtain biomass porous carbon loaded with nanosilicon material.
[0100] The performance tests were conducted on the Schwarzites carbon-supported nano-silicon materials prepared in Examples 1-8 and the biomass porous carbon-supported nano-silicon materials prepared in Comparative Example 1. The test results are shown in FIG. Figure 1-Figure 3 And as shown in Table 1.
[0101] At the same time, weigh 470 mg of Schwarzites carbon-loaded nano-silicon material prepared in Examples 1-8 and biomass porous carbon-loaded nano-silicon material prepared in Comparative Example 1, as well as 30 mg of carboxymethyl cellulose, add an appropriate amount of deionized water, use a planetary ball mill to mill for 2 hours, apply the milled slurry on the current collector, and cut it into a negative electrode sheet with a diameter of 12 mm after vacuum drying at 80°C for 12 hours. Use metallic lithium as the comparison electrode and reference electrode, PP diaphragm, LiPF6 with a concentration of 1 mol / L as the electrolyte, and a mixed solution of diethyl carbonate and ethylene carbonate with a volume ratio of 1:1 as the solvent, and assemble button batteries in a glove box with an argon atmosphere. The button batteries are then tested on the Xinwei battery test system, where the charge and discharge voltage range is 0V-2V, the current density is 0.2C, 1C=1000mA / g, and the test results are as follows: Figure 4-Figure 6 And as shown in Table 1.
[0102] Table 1
[0103]
[0104] It can be seen from Table 1 that the SP in Schwarzites carbon prepared using ZTC structure molecular sieve as template 2 With high component content, when Schwarzites carbon-loaded nano-silicon materials are used in negative electrode sheets, they can effectively alleviate the problem of breakage during rolling, and at the same time, they can better inhibit the volume expansion of silicon particles during the charging and discharging process.
[0105] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0106] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing Schwarzites carbon-supported nano-silicon material, characterized in that: The steps include: Using a molecular sieve with a ZTC structure as a template, chemical vapor deposition is carried out under the conditions of a protective atmosphere and a gaseous carbon source to obtain a molecular sieve-carbon composite material; removing the template in the molecular sieve-carbon composite material to obtain Schwarzites carbon; Using Schwarzites carbon as a carrier, chemical vapor deposition is carried out under the conditions of a protective atmosphere and a gas-phase silicon source to obtain a silicon-carbon composite material; The silicon-carbon composite material is carbon-coated to obtain Schwarzites carbon-loaded nano-silicon material.
2. The method for preparing Schwarzites carbon-supported nano-silicon material according to claim 1, characterized in that: The ZTC structured molecular sieve is at least one of zeolite LTA type molecular sieve, zeolite FAU type molecular sieve or zeolite EMT type molecular sieve.
3. The method for preparing Schwarzites carbon-supported nano-silicon material according to claim 1, characterized in that: The ZTC structured molecular sieve has a D 50 5μm-20μm.
4. The method for preparing Schwarzites carbon-supported nano-silicon material according to claim 1, characterized in that: The step of performing chemical vapor deposition under the conditions of a protective atmosphere and a gaseous carbon source satisfies at least one of the following conditions: (1) The gaseous carbon source is selected from at least one of acetylene, methane, ethylene, benzene or toluene; (2) The temperature of chemical vapor deposition is 500°C-2000°C and the time is 0.5h-10h; (3) The heating rate of chemical vapor deposition is 1℃ / min-10℃ / min; (4) The protective atmosphere is selected from at least one of nitrogen and inert gas.
5. The method for preparing Schwarzites carbon-supported nano-silicon material according to claim 1, characterized in that: The template in the molecular sieve-carbon composite material is removed by alkali washing or water washing at a temperature of 50°C-150°C.
6. The method for preparing Schwarzites carbon-supported nano-silicon material according to claim 1, characterized in that: The step of performing chemical vapor deposition under the conditions of a protective atmosphere and a gas phase silicon source satisfies at least one of the following conditions: (1) The gas phase silicon source is selected from at least one of silane, disilane, dichlorosilane or tetramethylsilane; (2) The temperature of chemical vapor deposition is 400°C-650°C and the time is 0.5h-5h; (3) The heating rate of chemical vapor deposition is 1℃ / min-10℃ / min; (4) The protective atmosphere is selected from at least one of nitrogen and inert gas.
7. The method for preparing Schwarzites carbon-supported nano-silicon material according to claim 1, characterized in that: The silicon-carbon composite material is carbon-coated by chemical vapor deposition, wherein the chemical vapor deposition step satisfies at least one of the following conditions: (1) the gaseous carbon source is selected from at least one of acetylene, methane, ethylene, benzene or toluene; (2) The heating rate of chemical vapor deposition is 1℃ / min-10℃ / min; (3) The temperature of chemical vapor deposition is 500°C-1000°C, and the time is 0.5h-3h; (4) Chemical vapor deposition is carried out under a protective atmosphere, wherein the protective atmosphere is selected from at least one of nitrogen or an inert gas.
8. A Schwarzites carbon-supported nano-silicon material prepared by the method for preparing Schwarzites carbon-supported nano-silicon material according to any one of claims 1 to 7.
9. A negative electrode sheet prepared using the Schwarzites carbon-loaded nano-silicon material as claimed in claim 8.
10. A secondary battery prepared using the negative electrode sheet as claimed in claim 9.
Citation Information
Cited By
Preparation method of silicon-carbon negative electrode material for regulating and controlling silicon deposition by using solid fluidizing medium
CN120497321A
